Association between endothelial activation and stress index and mortality in critically ill patients with atrial fibrillation: In MIMIC database: A Retrospective Cohort Study - Peiling Zuo; Huanhuan Zhu; Chunying Sun; Xiaohan Ma; Sheng Chen; Rong Tang; Tong Wu; Ding Zhang; Xiao Tang; Wenquan Lv; Wenzhong Chen; Xiawei Wei; et al. (PLoS ONE, 2026)
Background Evidence indicates that the Endothelial Activation and Stress Index (EASIX) is a predictor of mortality in endothelium-related conditions; however, its association with mortality risk in atrial fibrillation (AF) remains uncertain. Accordingly, this study examines the relationship between EASIX and mortality risk among patients with AF. Methods This retrospective analysis utilized data from the Medical Information Marketplace in Intensive Care IV (MIMIC-IV) database, which includes critically ill patients diagnosed with AF. To examine the association between EASIX scores and mortality, Kaplan–Meier survival analysis, Cox proportional hazards models, and restricted cubic spline regression were applied to evaluate the relationship between EASIX and all-cause mortality. Subgroup analyses were conducted to explore potential interactions with key patient characteristics, and sensitivity analyses were performed to further confirm the robustness of the results. Results A total of 3,193 patients were included in the analysis. KM survival analysis showed that elevated EASIX levels were associated with a higher risk of both in-hospital and ICU mortality. After adjusting for potential confounders, increased EASIX levels remained significantly associated with in-hospital mortality [HR, 1.09 (95% CI 1.03, 1.15), P = 0.0002] and ICU mortality [HR, 1.10 (95% CI 1.04, 1.17), P = 0.0002]. Stratified analyses revealed a significant interaction between sepsis, respiratory failure, and EASIX in relation to both in-hospital and ICU mortality. To evaluate the robustness of the findings, a sensitivity analysis was performed. After additionally adjusting for metoprolol and heparin as covariates, patients in the highest EASIX group continued to demonstrate the greatest mortality risk: the HR for in-hospital death was 2.08 (95% CI: 1.51–2.85), and the HR for ICU death was 1.83 (95% CI: 1.21–2.65). Conclusion Elevated EASIX levels correlate with higher mortality rates, underscoring its potential as an accessible tool for identifying high-risk patients and informing clinical decisions. However, further studies are needed to explore the underlying mechanisms and validate its applicability across diverse patient populations.